MENINGKATKAN KEMAMPUAN SOSIALISASI MELALUI METODE SOSIODRAMA PADA ANAK USIA 5-6 TAHUN DI PAUD TK AVIA KECAMATAN MARPOYAN DAMAI PEKANBARU - Julida Afrila; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase in child socialization skills through methods sociodramas in children aged 5-6 years in kindergarten early childhood Avia Marpoyan Peace District of Pekanbaru. This type of research is classroom action research conducted in two cycles. Data collection tool used in this research is a form of observation sheet. The number of samples in this study were 20 children consisted of 12 girls and 8 boys. Based on the analysis of the assessment process 2 cycles increased. The results of this study are very satisfying because getting the average value highly significant from before action to the first cycle and from the first cycle to the second cycle, ie from an average value of 40.31 increased to 49.68 and increased again to 73.85. From the results of these studies concluded that learning by using sociodramas give a positive response to the child and can improve social skills in children.Keywords: Ability Socializing, Metode Sociodramas